THE RELATIONSHIP BETWEEN BODY IMAGE AND SELF-ACCEPTANCE IN PATIENTS UNDERGOING HEMODIALYSIS - Lono Wijayanti; Mitha Wulan Anggraini; Siti Nurjanah; Faridah Umamah (Nurse and Holistic Care)
Introduction: Hemodialysis is a medical procedure that often causes significant physical changes, such as weight loss, swelling, and skin changes that can affect the patient's body image. The long-term process of hemodialysis also has the potential to interfere with psychological conditions, especially patient self-acceptance.